Determination of Corporate Social Responsibility Disclosure Based on the Ownership Structures: Evidence from Companies Listed on SRI-KEHATI Index - Rahmawaty Rahmawaty; Putra Maswan (Universitas Syiah Kuala, 2020)
Objective – The ownership structure dispersed into state ownership, foreign ownership, institutional ownership, and corporate ownership. This study aims to examine the influence of ownership structure on Corporate Social Responsibility Disclosure which is measured by 40 Corporate Social Responsibility indicators developed by Dias in 2017. Design/methodology – This study utilizes the samples from companies listed on SRI-KEHATI Index for the year 2013-2017. Purposive sampling technique was applied resulting in 9 companies were chosen for a total 45 observation data. Multiple linear regression analysis is utilized for the hypotheses testing. Results – The result of this study revealed that all independent variables simultaneously influenced the dependent variable. Partially, foreign ownership and institutional ownership determined the Corporate Social Responsibility Disclosure, but there is no influence for state ownership and corporate ownership on Corporate Social Responsibility Disclosure.